2019
DOI: 10.1007/s10555-019-09796-3
|View full text |Cite
|
Sign up to set email alerts
|

Acidosis and proteolysis in the tumor microenvironment

Abstract: The glycolytic phenotype of the Warburg effect is associated with acidification of the tumor microenvironment. In this review, we describe how acidification of the tumor microenvironment may increase the invasive and degradative phenotype of cancer cells. As a template of an extracellular acidic microenvironment that is linked to proteolysis, we use the resorptive pit formed between osteoclasts and bone. We describe similar changes that have been observed in cancer cells in response to an acidic microenvironme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
57
0
8

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(65 citation statements)
references
References 91 publications
0
57
0
8
Order By: Relevance
“…Acidosis has been reported as one of the early events in solid tumours and is defined as a characteristic of the tumour microenvironment [35]. Given that acidosis is a stressor and select cancer cells are suited for an acidic microenvironment, targeting tumour acid homeostasis would be potential strategies.…”
Section: Discussionmentioning
confidence: 99%
“…Acidosis has been reported as one of the early events in solid tumours and is defined as a characteristic of the tumour microenvironment [35]. Given that acidosis is a stressor and select cancer cells are suited for an acidic microenvironment, targeting tumour acid homeostasis would be potential strategies.…”
Section: Discussionmentioning
confidence: 99%
“…Valcz et al identified the most aberrantly expressed MVB markers and revealed the transition of diffuse ALIX signals into a MVB-like pattern during the adenoma-carcinoma sequence, which may provide clues to revealing the interactions between cancer and the surrounding microenvironment, particularly those involving the regulation of tumor growth and metastatic invasion [148]. Moreover, the formation of invadopodia (see above) in many types of cancer drives cell invasion, depending on enhanced MVB docking and fusion with the plasma membrane [85,102,149]. Therefore, we believe that invadopodia formation is the first step in tumor cell invasion and metastasis, in which MVB-mediated transport of MMPs to degrade the extracellular matrix is an important step [85,89,102,149].…”
Section: Mvbs and Metastasis In Cancermentioning
confidence: 99%
“…Moreover, the formation of invadopodia (see above) in many types of cancer drives cell invasion, depending on enhanced MVB docking and fusion with the plasma membrane [85,102,149]. Therefore, we believe that invadopodia formation is the first step in tumor cell invasion and metastasis, in which MVB-mediated transport of MMPs to degrade the extracellular matrix is an important step [85,89,102,149]. A recent study revealed that VAMP3-dependent secretion of MT1-MMP enhances the degradation of the extracellular matrix, and induces cancer cell invasion [102].…”
Section: Mvbs and Metastasis In Cancermentioning
confidence: 99%
“…[1][2][3][4] However, abnormal intracellular pH is associated with cellular dysfunctions such as cancer and neurodegenerative disorders. 5,6 Hydrogen peroxide (H 2 O 2 ), an important member of reactive oxygen species (ROS) mediates signal cascades involved in redox homeostasis. 7 Substantial evidence has showed that excessive H 2 O 2 is relevant to serious diseases including cardiovascular disorders, neurodegenerative diseases, cancer and diabetes.…”
Section: Introductionmentioning
confidence: 99%